Complementary feeding practices of children aged six months to two years - Thoker, Wasim Yousuf; Tariq, Syed; Bhat, Aijaz Ahmad (International Journal of Contemporary Pediatrics, 2025)
Background: As infants grow and become more active following the first 6 months of life, breast milk alone falls short of providing the full nutritional requirements. This is a very vulnerable period. It is the time when malnutrition starts in many infants contributing to the high prevalence of malnutrition in this age group. Complementary feeding plays critical role in bridging these gaps. Methods: This hospital based cross sectional study was conducted in Department of Pediatrics GMC Srinagar, over 2 years from November 2019 to November 2021. The study participants were infants and young children, aged 6 to 24 months. Mothers/caregivers were the primary target as respondents. Total sample size was 400. Results: The median age of the mothers was 24 years. 90% children consumed foods made from grains, roots and tubers. Vitamin-A rich foods were consumed by 45%, dairy products by 32%, legumes and nuts by 18 % of the children aged 6 months-23 months. Consumption of animal origin foods was low, barely 5% and 13% children consumed eggs and flesh foods respectively. The mean dietary diversity score was 2.4. Conclusions: The results of this review indicate that effectively implemented provision of complementary feeding and education on complementary feeding have a potential to prevent undernutrition in children. Despite clear evidence of the disastrous consequences of childhood nutritional deprivation in the short and long terms, nutritional health remains a low priority. Therefore, enhanced and rigorous actions are needed to deliver and scale up nutritional education and complementary feeding interventions.